Is China's Enterprise Employees' Basic Pension Plan Sustainable? Evidence from Two Northeastern Provinces in the Double-Drop Era. Issue 1 (2nd January 2023) - Tang, Yunshu; Ma, Wen; Zhou, Qiaoyun
ABSTRACT: In 2019, the Chinese central government adopted the "double-drop" policy (to reduce both the rate and the base of employers' contributions to employees' basic pension plan) as an attempt to increase overall employment and plan coverage in the national labor market and, in turn, achieve a balance in the plan's annual contributions and benefits at the provincial level. Accordingly, we utilize the cohort element method and actuarial models to explore the policy's effects on the plan's financial sustainability in both the short and long term based on data from Heilongjiang and Liaoning provinces in northeastern China. We further examine the policy's indirect effects (through changes in the compliance rate, enterprises' overall employment rate, coverage rates, or economic growth rates) on the plan's sustainability using the circulation substitution method. We find that, although the policy directly reduces employer contributions, it indirectly improves the plan's balance between contributions and benefits through changes in employment, coverage, compliance, or economic growth rates. Nevertheless, the overall effect of the policy is far weaker than its negative effect. Hence, we provide a portfolio of solutions that includes increases in provincial governments' subsidies (to approximately 8% of total fiscal expenditures), increases in the central government's adjustment proportion (to 11%–15%), and delays in the retirement age (progressively to age 65).